Indigenous nuts of the South Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Market development for selected South Pacific indigenous tree nuts by Michael W Brown 1996 87pp Pbk ISBN 982 175 119 9